The Impacts of Minimum Wage On Employers' Employment Strategies and Employees' Behaviour in Malaysia's Hospitality Industry: A Pitch - Kun Hing Yong (Journal of Accounting and Management Information Systems (JAMIS), 2019)
This pitch letter summarizes my personal reflections of employing the pitching research template created by Faff (2015, 2018) to my PhD research topic. It explains how the template guides the author to articulate and conceptualize a research idea critically, clearly, systematically and effectively. Specifically, this letter positively supports the use of the pitching research template, in particular for new PhD student or novice researcher during their early stage of research process.
Keywords: J21; J38; L83; 650; Pitching research; minimum wage; employment strategies; employees' behavior; hospitality